Cuba's National School of Ballet: Redefining a structural icon. (1st February 2020) - Douglas, Isabella; Napolitano, Rebecca K.; Garlock, Maria; Glisic, Branko
Highlights: Reinforced concrete was efficiently blended with thin-tile vaulting FEM was used to understand the construction process and choices Preservation plans should account for mixed construction typology Abstract: The National School of Ballet is one of five art schools designed in Havana, Cuba during the reign of Fidel Castro. While construction of the schools started in the early 1960s, it was halted before the building was completed resulting in the eventual abandonment of the school. Currently, the school is in a state of disrepair and preservation plans are being drafted to restore it. Historically, it was thought that many of the large spans in the ballet complex were constructed using an approach called thin-tile vaulting. However, during fieldwork in Havana, the authors found that despite surface-level appearances, the complex is not entirely constructed with thin-tile vaulting. In many cases, a surface-level of thin-tile vaulting covers reinforced concrete structural systems. The objective of this work is to understand and document the structural systems of the National Ballet School, specifically the main dome. The buildings were documented using terrestrial photography and spherical imaging; structural analysis of the main dome was carried out using a combination of analytical and numerical methods. By combining these methods, it was found that the design of the National Ballet School economically, elegantly, and efficiently blends reinforced concrete with thin-tile vaulting to showcase the mastery of the engineers and builders.